Pengembangan Pemasaran Susu Kambing Melalui Media Sosial pada CV Rokir Farm, Kabupaten Agam, Sumatera Barat - Ratni Prima Lita; Indri Juliyasri; Sri Melia; Devi Yulia Rahmi; Fatma Poni Mardiah; Meuthia Meuthia; Rahmat Eka Putra (Warta Pengabdian Andalas, 2023)
CV Rokir Farm, Agam Regency, West Sumatra Province, produced a long-established business. It is engaged in dairy farming to produce goat's milk. The main problem is developing product quality that can upgrade the marketing product's performance. This community service activity aimed to increase business growth, develop product competitiveness to reach markets outside the Agam Regency and accelerate the diffusion of technology and management from universities to partners. The activity was carried out in 3 stages: preparation, implementation, monitoring and evaluation. The result of this activity was an increase in promotion through social media. This activity resulted in several suggestions, such as 1) Partners are invited to continue activities to control the production process from raw materials to finished products, 2) Partners continue to increase the use of social media for online marketing and increase traditional marketing to expand marketing, 3) Computer investment is needed for development products, 4) It is necessary to develop galleries and farmer's cooperatives to help business growth, and 5) There is a need for vigorous promotion to market products.